PENGEMBANGAN SKALA KEPRIBADIAN SISWA SMA DARI TIPOLOGI KEPRIBADIAN JUNG DAN MYERS-BRIGGS - Jelpa Periantalo; Saifuddin Azwar (Jurnal Sains Sosio Humaniora, 2017)
The purpose of this research is to construct personality scale from Jung and Myers-Briggs personality type. Basic concept of personality type is human has four dimensional aspects. The dimensional consists of two personality type which is contrary. There are extrovert-introvert, sensing-intuition, thinking-feeling and judging-perceiving. Each human has this two contrary personality. But, one is dominant. Four combination of dominant personality aspect will make a personality type. The personality type can be used for student strategic learning, teacher teaching strategy, psychological counseling, identification of potential and recommendation for higher education program. Item format used question with two answers (a and b). Research subject was about 250 highs school students. There were 146 of 240 items which passed through selection. The final format scale uses 60 items which presents four dimensional aspects. Face, logic and construct validity were used in research. There were no correlations among four dimensional aspects of personality type. This shown good construct (discriminant) validity. Test retest reliability coefficient with one day interval was 0,91 and 0,81 for one week interval. The Scale can be used both for research and practice in psychology.